Om Grundtvigs tidsopfattelse - Michelsen, William (Grundtvig-studier, 1976)
Concerning Grundtvig's Conception of Timeby William Michelsen With a quotation from P. G. Lindhardt as its starting-point Dr. Michelsen’s article maintains that Søren Kierkegaard and his successors misinterpreted Grundtvig’s Christian preaching because the two Christians had a different conception of time. Kierkegaard began with Kant’s theory of time as an a priori idea, whereas Grundtvig regarded time as the concrete expression of the limited existence of man and the world in contrast to God’s boundlessness. Since both Grundtvig’s and Kierkegaard’s contemporaries and successors based their philosophy and theology on Kant’s a priori idea, which Grundtvig did not accept, he has not been understood as a philosopher. There has been a tendency to regard him on the same level as the German Idealists (Schelling and Hegel), even though he broke with them in Oct. 1813 and instead built his thought on the Bible and pre-Kantian philosophy, also with regard to his conception of time. He thus accepted the Biblical idea of creation, which Kant and his successors rejected.